2018
DOI: 10.1007/s00330-018-5680-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric ultrasomics of significant liver fibrosis: A machine learning-based analysis

Abstract: • Multiparametric ultrasomics has achieved much better performance in the discrimination of significant fibrosis (≥ F2) than the single modality of conventional radiomics, original radiofrequency and contrast-enhanced micro-flow. • Adaptive boosting, random forest and support vector machine are the optimal algorithms for machine learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 39 publications
2
73
0
Order By: Relevance
“…Feature selection and classification can be performed together as a single process or separately using different algorithms. Unreliable features may be excluded prior to feature selection and classification, based on the results of interor intra-observer agreement or test-retest repeatability analyses (6,11,(17)(18)(19)(20)(21). To reduce redundancy in the features, informative features showing a high dynamic range may be selected among the correlated features in hierarchical feature clustering (18,22).…”
Section: Process Of Radiomics Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Feature selection and classification can be performed together as a single process or separately using different algorithms. Unreliable features may be excluded prior to feature selection and classification, based on the results of interor intra-observer agreement or test-retest repeatability analyses (6,11,(17)(18)(19)(20)(21). To reduce redundancy in the features, informative features showing a high dynamic range may be selected among the correlated features in hierarchical feature clustering (18,22).…”
Section: Process Of Radiomics Analysismentioning
confidence: 99%
“…Traditional statistical methods may not be successful in dealing with high-dimensional radiomics features (i.e., too many variables relative to the number of observations). A number of machine learning methods have therefore been used for feature selection and/or classification (10,21,23,24). Among the methods for feature selection and classification, regression with Ridge, least absolute shrinkage and selection operator (LASSO), and elastic net regularization have been commonly used (6, 10-13, 17, 19, 25, 26), likely because these algorithms allow for the development of a regression model that is more familiar to radiologists than other machine learning classifiers.…”
Section: Process Of Radiomics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, a total of 78 articles were included in the qualitative analysis, of which 17 were included in the quantitative analysis (15 studies on liver brosis and 2 studies on NAFLD). There were 11 studies integrating AI with imaging modalities, i.e., ultrasonography (21)(22)(23)(24)(25) , elastography (26,27) , computed tomography (CT) (28,29) and magnetic resonance imaging (MRI) (30,31) , to facilitate the diagnosis of liver brosis and NAFLD. The other 6 studies developed AI models using clinical and laboratory data, such as the presence of other underlying diseases or ascites, liver chemistry tests, and platelet and white blood cell counts, to predict liver brosis stages (32)(33)(34)(35)(36)(37) .…”
Section: Literature Searchmentioning
confidence: 99%
“…For example, a study that followed 11,448 subjects for 5 years showed that the incidence of a disease was 12% (n = 1,418) [1]. Another cohort study followed 77,425 free of liver disease subjects for 4.5 years, 10,340 of them have developed the disease [2]. In general, more than 75% of liver tissue requires to be affected before the function of the liver is decreased [3].…”
Section: Introductionmentioning
confidence: 99%